2005
DOI: 10.1681/asn.2004030208
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Development of Decreased Kidney Function in a Southeast Asian Population

Abstract: End-stage kidney disease has become an increasing burden in all regions of the world. However, limited epidemiologic data on chronic kidney disease in Southeast Asian populations are available. Therefore, a cohort study over a period of 12 yr (1985 to 1997) in 3499 employees of the Electric Generation Authority of Thailand, aged 35 to 55 yr, was conducted to determine the prevalence of decreased kidney function and risk factors associated with future development of decreased kidney function. The prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
139
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(155 citation statements)
references
References 40 publications
12
139
3
1
Order By: Relevance
“…Keeping in mind the generally known influence of alcohol consumption on UA levels as well as its possible protective influence on the outcome, we found an evaluation of its influence interesting. 13 In this study, the effect was weak, the OR for the outcome variable remained nearly unchanged, and confounding could have been explained by only 2% in both elevated UA groups.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Keeping in mind the generally known influence of alcohol consumption on UA levels as well as its possible protective influence on the outcome, we found an evaluation of its influence interesting. 13 In this study, the effect was weak, the OR for the outcome variable remained nearly unchanged, and confounding could have been explained by only 2% in both elevated UA groups.…”
Section: Discussioncontrasting
confidence: 48%
“…A few studies have found that hyperuricemia is associated with an increased risk for new-onset kidney disease, 13,14 but this association could be confounded by some metabolic factors and other risk factors that were not included in these previous studies. A confounder model was performed to provide epidemiologic evidence for UA as a possible independent risk factor for the development of incident kidney disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were also found in Japan and Thailand. 20,21 Hence, the level of serum uric acid in CKD patients, especially in those with eGFR <90 mL/min/1.73 m 2 , should be appropriately monitored during the management of CKD. CVD and cerebrovascular diseases are risk factors associated with early renal injury in patients with CKD in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a subdivision of the previously described GFR stage 3 has been proposed to help further define the severity of kidney dysfunction in patients with CKD 25 . Risk factors for the development of reduced kidney function in Southeast Asian populations have been identified and include the presence of diabetes, systolic hypertension (>159 mmHg), hyperuricemia (>6.29 mg/dL), elevated BMI (>24.9 kg/m 2 ) and hypercholesterolemia (>248.3 mg/dL) 26 .…”
Section: Diabetes and Chronic Kidney Disease Complications In Asiamentioning
confidence: 99%